Revisiting the Nabberör Boat Grave : A Multiproxy Analysis of a Vendel Period Multiple Burial on the Swedish island of Öland - Ekengren, Fredrik ; 0000-0003-3753-3073; Macheridis, Stella ; 0000-0002-7315-5623; Wilhelmson, Helene; Jennbert, Kristina ; 0000-0002-5839-401X; Iregren, Elisabeth (Praehistorische Zeitschrift, 2025)
This paper presents a reflexive, transdisciplinary reassessment of the Nabberör boat grave, dated to the 8th century CE, on the Baltic island of Öland. The osteological material and the grave goods are carefully re-examined and recontextualised using a multiproxy approach, including new archaeological, bioarchaeological, zooarchaeological, isotopic, and aDNA analyses. The results reveal a multiple burial of remarkable complexity, containing between 10 and 12 individuals – males and females, adults and children – as well as five dogs, two horses, one goat, at least one sheep/goat, one pig, and one bird. The bone chemical and osteological analyses, as well as the analysis of the artefacts, suggest an elite kin group belonging to a wide socio-political network that spanned the Baltic Sea. This study demonstrates the value of revisiting old excavations, and expands our understanding of the boat grave custom on the cusp of the Viking Age.
Keywords: Boat grave; Multiple burial; Vende Period; Merovingian Period; Böda; Multiproxy archaeology; Bioarchaeology; Zooarchaeology; Stable isotope analysis; aDNA; Reflexive archaeology; Burial taphonomy; grave reopening